Science for All Americans. - Rutherford, F. James (Oxford University Press, USA, 1991)
In order to compete in the modern world, any society today must rank education in science, mathematics, and technology as one of its highest priorities. It's a sad but true fact, however, that most Americans are not scientifically literate. International studies of educational performance reveal that U.S. students consistently rank near the bottom in science and mathematics. The latest study of the National Assessment of Educational Progress has found that despite some small gains recently, the average performance of seventeen-year-olds in 1986 remained substantially lower than it had been in.